Modelling Phase Change Material for Concentrating Energy Storage in Solar Thermal Cooking Stove - Ang, Chan Mun; Hagos, F. Y.; R., Mamat; A. N., Oumer; Azmi, W. H. (Universiti Selangor (UNISEL), 2015)
Nowadays, cheaper and cleaner alternative energy source is a compulsory globally due to complex challenges with the conventional ones.